Clinical practice guidelines—Nursing management for pediatric patients with small bowel or multivisceral transplant. Issue 1 (8th November 2013) - Bodeur, Cynthia; Aucoin, Julia; Johnson, Raeanne; Garrison, Kaitlyn; Summers, Amanda; Schutz, Kristen; Davis, Megan; Woody, Sherri; Ellington, Kelly
Abstract Purpose Small bowel or multivisceral transplant is a relatively new treatment for irreversible intestinal damage, and no published practice guidelines exist. The purpose of this article is to report evidence regarding the best plan of care to achieve adequate nutrition and appropriate development for children. Design and Methods An integrative review was conducted with 54 articles related to management of this transplant population. A nine‐member nursing team integrated the findings. Practice Implications This resulting guideline represents the best research and best practices on which to base staff education and competency validations to manage this medically fragile patient population.